Analysis of the Genome Wide Sequence of Yersinia pestis strains Based on the Consecutive 680-SNP Algorithm - G. N. Odinokov; G. A. Eroshenko; Ya. M. Krasnov; L. M. Kukleva; A. V. Cherkasov; N. Yu. Shavina; V. V. Kutyrev (Проблемы особо опасных инфекций, 2013)
Designed is an optimized scheme for SNP analysis of the genome wide sequences of plague agent strains, based on the consecutive algorithm of clusterization of individual intraspesific Y. pestis groups. The scheme comprises 680 singular polymorphic nucleotides (SNPs), the usage of which provides not only for the clustering of closely related strains, but for the determination of phylogenetic bonds between groups of strains and order of their divergence from the common tree-trunk of the plague agent evolution. Based on the consecutive 680-SNP algorithm, carried out is the analysis of genome wide sequences of C-627 Y. pestis strain isolated in Central-Caucasian high-mountain focus (Russia), strain 1454 isolated in Altay mountain focus (Russia), strain 231 (708) – Aksay high mountain focus (Kirgizia), and vaccine EV NIIEG (Research Institute of Epidemiology and Hygiene) strain, applied for immunization in the Russian Federation and in a number of other countries. Identified are the genome variants of the strains: 1. ORI3 (EV NIIEG), 2. MED0 (C-627), 0.ANT3 (231(708)), 0.ANT4 (1454), and their place in the scheme of Y. pestis global variation. Evidenced is the absence of the chromosomal region responsible for pigmentation in the genome wide sequence of the vaccine strain EV NIIEG, which testifies to its safe use for specific plague prophylaxis.